Supply chain management and management science: A successful marriage - Rezaei, Jafar; Olson, David L.; Sarkis, Joseph (Journal of Supply Chain Management Science, 2020)
The last century has witnessed extant studies on the applications of Management Science (MS) to a diverse set of Supply Chain Management (SCM) issues. This paper provides an overview of the contribution of MS within SCM. A framework is developed in this paper with a sampling of MS contributions to major SCM dimensions. Future research directions are presented.